Impact of a probiotic chewable tablet on stool habits and microbial profile in children with functional constipation: A randomized controlled clinical trial - Gan, Dan; Chen, Jialun; Tang, Xin; Xiao, Luyao; Martoni, Christopher J.; Leyer, Gregory; Huang, Guixia; Li, Wei (Frontiers in Microbiology, 2022)
Constipation is a common and typically multifactorial childhood complaint, and the clinical management of childhood functional constipation is challenging. A randomized, single-blind, placebo-controlled, multi-center clinical trial was conducted in 92 children (47 from Beijing, China and 45 from Shanghai, China) aged 4 to 12 with functional constipation according to Rome III criteria. Children were assigned to receive a probiotic chewable tablet (5 × 109 CFU/day, n = 47), consisting of Lactobacillus acidophilus DDS®-1 and Bifidobacterium animals subsp. lactis UABla-12™ or placebo (n = 45), twice daily for 4 weeks, followed by a week follow-up period. Results suggested that the probiotic group showed a faster and more pronounced normalization of stool frequency over the intervention period (3.15 vs. 1.83) when compared to placebo group (2.51 vs. 1.87). Meanwhile, the percentage of subjects with hard defecation decreased from 43% to 14% in the probiotic group, while the percentage of subjects with normal defecation increased from 56% to 80% in the probiotic group, further confirming the normalization of stools habits. This randomized controlled trial demonstrated the potential of a probiotic chewable tablet containing L. acidophilus DDS®-1 as a daily probiotic dosage form for children with functional constipation.